Incidence and Survival of Hepatocellular Carcinoma in Type 2 Diabetes Patients with Cirrhosis Who Were Treated with and without Metformin - Tangjarusritaratorn T (Dove Medical Press, 2021)
Thanida Tangjarusritaratorn,1 Watip Tangjittipokin,1,2 Tada Kunavisarut3 1Department of Immunology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand; 2Siriraj Center of Research Excellence in Diabetes and Obesity, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand; 3Division of Endocrinology & Metabolism, Department of Medicine, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Tada KunavisarutDivision of Endocrinology & Metabolism, Department of Medicine, Faculty of Medicine Siriraj Hospital, Mahidol University, 2 Prannok Road, Bangkoknoi, Bangkok, 10700, ThailandTel +66 2-419-7799Fax +66 2-419-7792Email kunavisarut@gmail.comPurpose: To evaluate metformin’s benefit on the incidence and survival of hepatocellular carcinoma (HCC) in cirrhosis with type 2 diabetes mellitus (T2DM) patients.Patients and Methods: We conducted a retrospective study from 2006 to 2019. The patients were assigned to metformin exposure if they administered metformin at least 3 months after diagnosis of cirrhosis. The outcomes were incidence and survival of HCC in T2DM with cirrhosis treated with metformin compared with those who were not treated with metformin. For the incidence of HCC, the follow-up time was 5 years after cirrhosis was diagnosed. For the survival of HCC, we censored for vital status in June 2019.Results: Of 1061 patients, the patients were divided into 719 patients with metformin exposure and 342 in metformin non-exposure. In metformin exposure, 125 patients (17.4%) developed HCC. In metformin non-exposure, 128 patients (37.4%) developed HCC. Metformin exposure had a significantly lower risk of developing HCC in multivariate analysis HR 0.48 (0.36– 0.61); P< 0.001. For the survival of HCC, 327 patients were recruited. One-hundred and sixty-two patients were in metformin exposure and 165 patients were in metformin non-exposure. Sixty patients (37%) in metformin exposure died, while 84 patients (50.9%) in metformin non-exposure died. The median survival of metformin exposure and metformin non-exposure were 6.9 years and 3.88 years, respectively; P=0.003. In univariate analysis, the metformin exposure was significantly associated with better survival than in the non-exposure group, HR 0.63 (0.45– 0.88); P=0.006. No significant difference was observed in multivariate analysis between two groups, HR 1.07 (0.74– 1.54); P=0.72.Conclusion: Metformin exposure was associated with a lower incidence of HCC in cirrhosis with T2DM patients and seemed to extend survival. Continuing metformin in patients with cirrhosis with T2DM should be considered if there was no contraindication.Keywords: type 2 diabetes mellitus, cirrhosis, hepatocellular carcinoma, metformin